Arg156 in the AP2-Domain Exhibits the Highest Binding Activity among the 20 Individuals to the GCC Box in BnaERF-B3-hy15, a Mutant ERF Transcription Factor from Brassica napus - Zhuang, Jing; Li, Meng-Yao; Wu, Bei; Liu, Yan-Jun; Xiong, Ai-Sheng (Frontiers in Plant Science, 2016)
To develop mutants of the ERF factor with more binding activities to the GCC box, we performed in vitro directed evolution by using DNA shuffling and screened mutants through yeast one-hybrid assay. Here, a series of mutants were obtained and used to reveal key amino acids that induce changes in the DNA binding activity of the BnaERF-B3 protein. With the BnaERF-B3-hy15 as the template, we produced 12 mutants which host individual mutation of potential key residues. We found that amino acid 156 is the key site, and the other 18 mutants host the 18 corresponding individual amino acid residues at site 156. Among the 20 individuals comprising WT (Gly156), Mu3 (Arg156), and 18 mutants with other 18 amino acid residues, Arg156 in the AP2-domain is the amino acid residue with the highest binding activity to the GCC box. The structure of the α-helix in the AP2-domain affects the binding activity. Other residues within AP2-domain modulated binding activity of ERF protein, suggesting that these positions are important for binding activity. Comparison of the mutant and wild-type transcription factors revealed the relationship of protein function and sequence modification. Our result provides a potential useful resource for understanding the trans-activation of ERF proteins.